PELATIHAN MEMBUAT VIDEO PEMBELAJARAN MENARIK DENGAN SMARTPHONE PADA GURU ADZKIA - Widdya Rahmalina; Meria Ultra Gusteti; Evi Desmariani (LPPM Universitas Abdurrab, 2020)
The Covid-19 pandemic that hit the world had an impact on the world of education where schools carried out the Teaching and Learning Process by online , one of which was the Adzkia Integrated Islamic school at the TK and SD levels. Since PBM is conducted online, the teachers only give assignments via group WhatsApp to students such as reading books, practice questions, etc. This makes learning monotonous and students get bored, so it is necessary to increase teacher qualifications in making interesting learning media such as instructional videos. Therefore, community service is carried out in the form of training in making interesting learning videos using smartphone. The training method is in the form of a demonstration of making a good learning video, direct practice methods with assistance in terms of making video and video editing using the kinemaster application, and assignment methods and competitions for making learning videos. This service aims to make Adzkia Integrated Islamic Kindergarten and SD teachers make interesting learning videos so that students are still excited about learning at home even though by online. The result of this service activity is that teachers can understand how to make learning videos and are skilled at using the kinemaster android application to edit videos to make them more interesting. In addition, since the training was held until now, teachers have applied the knowledge of making learning videos in PBM by online which are also shared on YouTube.